Brugada syndrome: different experimental models and the role of human cardiomyocytes from induced pluripotent stem cells - Li, Yingrui; Lang, Siegfried; Akın, Ibrahim; Zhou, Xiao-Bo; El-Battrawy, Ibrahim (Journal of the American Heart Association, 2022)
Brugada syndrome (BrS) is an inherited and rare cardiac arrhythmogenic disease associated with an increased risk of ventricular fibrillation and sudden cardiac death. Different genes have been linked to BrS. The majority of mutations are located in the SCN5A gene, and the typical abnormal ECG is an elevation of the ST segment in the right precordial leads V1 to V3. The pathophysiological mechanisms of BrS were studied in different models, including animal models, heterologous expression systems, and human‐induced pluripotent stem cell-derived cardiomyocyte models. Currently, only a few BrS studies have used human‐induced pluripotent stem cell-derived cardiomyocytes, most of which have focused on genotype-phenotype correlations and drug screening. The combination of new technologies, such as clustered regularly interspaced short palindromic repeats (CRISPR)/Cas9 (CRISPR associated protein 9)‐mediated genome editing and 3‐dimensional engineered heart tissues, has provided novel insights into the pathophysiological mechanisms of the disease and could offer opportunities to improve the diagnosis and treatment of patients with BrS. This review aimed to compare different models of BrS for a better understanding of the roles of human‐induced pluripotent stem cell-derived cardiomyocytes in current BrS research and personalized medicine at a later stage.
Gesehen am 23.03.2023